Circulating Exosome Involves in the Pathogenesis of Autoimmune Thyroid Diseases Through Immunomodulatory Proteins - Jia, Xi; Zhai, Tianyu; Zhang, Jin-an (Frontiers in Immunology, 2021)
Autoimmune thyroid diseases (AITDs) are chronic organ-specific autoimmune diseases, mainly including Graves’ disease (GD) and Hashimoto's thyroiditis (HT). Exosomes, as extracellular vesicles, contain a variety of biologically active substances which play a role in information exchange, thereby affecting the occurrence and progression of diseases. However, it is unclear whether exosomes are involved in the pathogenesis of AITDs. In this study, the role of exosomes in AITDs was explored from a proteomics perspective. Plasma exosomes were isolated from 12 patients with GD, 10 patients with HT and 7 normal controls (NC). Protein profiles were detected using the data independent acquisition (DIA) method and analyzed to investigate changes in plasma exosome proteins. In the setting of GD, 11 proteins were upregulated while 197 proteins were downregulated compared with healthy people. Among them, MAP1S (log2 FC=4.669, P=0.009) and VAMP8 (log2 FC=3.216, P=0.003) being the most significantly upregulated and RSU1 (log2 FC=-6.797, P = 0.001), ACTB (log2 FC=-4.795, P<0.001) and CXCL7 (log2 FC=-4.674, P<0.001) being the most significantly downregulated. In the cases of HT, HGFL (log2 FC=2.766, P=0.001), FAK1(log2 FC=2.213, P<0.001) and PTN12 (log2 FC=1.624, P<0.001) were significantly upregulated, while PSMF1 (log2 FC=-3.591, P< 0.001), PXL2B (log2 FC=-2.622, P=0.001) and CYTM (log2 FC=-1.609, P<0.001) were most downregulated. These differential proteins were mainly enriched in the immune system and metabolic system, indicating that plasma exosomes may play an important role in systemic immune imbalance in AITDs.